Depression score mediate the association between a body shape index and infertility in overweight and obesity females, NHANES 2013-2018 - Qiangwei Pan; Xiaolu Shen; Hongfeng Li; Bo Zhu; Dake Chen; Jiajia Pan (BMC, 2023)
Abstract Background Overweight and obese females demonstrate a significantly increased risk of anovulatory infertility. This study aims to investigate whether depression score could mediate the association between a body shape index (ABSI) and infertility, especially in overweight and obese population. Methods We included 5431 adult female Americans from the National Health and Nutrition Examination Survey (NHANES, 2013-2018) database. ABSI manifested the body shape using waist circumference, weight, and height. Infertility or fertility status was defined by interviewing female participants aged ≥ 18 through the reproductive health questionnaires. Depression symptoms were assessed using the Patient Health Questionnaire-9 (PHQ-9) with total scores between 0 and 27. To investigate the association of infertility with ABSI and other individual components, survey-weighted multivariable logistic regression was performed. Mediation analysis of PHQ-9 score was conducted to disentangle the pathways that link ABSI to infertility among the NHANES participants. Results 596 (10.97%) females were categorized with having infertility among 5431 participants. Participants with infertility showed higher ABSI and PHQ-9 score, appearing greater population proportion with depression symptoms. In the multivariable logistic regression model, ABSI (adjusted odds ratio = 0.14, 95% CI: 0.04 to 0.50) and PHQ-9 (adjusted odds ratio = 1.04, 95% CI: 1.01 to 1.07) were positively associated with infertility. PHQ-9 score was estimated to mediate 0.2% (P = 0.03) of the link between ABSI and infertility in all individuals, but to mediate 13.5% (P < 0.01) of the ABSI-infertility association in overweight and obese adult females. Conclusion The association between ABSI and infertility seems to be mediated by depression symptoms scored by PHQ-9, especially in those adult females with overweigh and obesity. Future studies should be implemented to further explore this mediator in ABSI-infertility link.